An Analysis of Code-Switching Used by English Study Program Students Through WhatsApp Group - Lubis, Muhammad AL Hudaifi; Suppriusman, Suppriusman; Safriyanti, Maria (Indonesian Journal of Education and Development Research, 2025)
This study Investigated the types and reasons for code-switching used by students of the English Study Program at Riau University in WhatsApp group communication. As digital communication has increasingly expanded into academic and social interactions, code-switching has emerged as a common linguistic behavior among bilingual and multilingual speakers. By employing a qualitative content analysis approach, the researcher analyzed WhatsApp chat logs from WhatsApp groups and conducted semi-structured interviews with selected participants. The findings show that intra-sentential switching is the most frequently used type, followed by tag switching and inter-sentential switching. Most students inserted English terms such as “deadline” or “handle conclusion” within Indonesian sentences, reflecting their bilingual proficiency and exposure to academic discourse. The main reasons for code-switching include linguistic competence, social identity and solidarity, situational context, audience design, and the need for emphasis or clarification. The results of this study highlight how students adapt their language use to fit the communicative context in digital academic spaces, reflecting their bilingual identity and pragmatic language strategies.